A Study on the Effect of Advertising Media on Malaysia Consumers’ Brand Awareness and Purchase Intention toward Food Products - Hue, Shin Yen (2014)
The purpose of the study are to explore the effects among advertising, brand awareness, and customer purchase intention. The samples are collected from citizens living in Klang Valley and the techniques used in this study are descriptive analysis, normality test, correlation analysis and regression analysis. The overall results show there are significant relationships between dependent variables (purchase intention) and independent variables measured by TV advertising, online advertising, press advertising and other demographic factors such as age, gender, marital status, education, occupation and etc. The study suggests that marketers need to put effort to observe the relationship with customers and try to define how they judge for the brand. The proper strategies need to implement to build up the awareness in customers’ mind. The values add products based on customer preference are important to satisfied customers and increase their level of interest and desire.